The impact of entrepreneurship research on other academic fields - A. Roy Thurik; David B. Audretsch; Jörn H. Block; Andrew Burke; Martin A. Carree; Marcus Dejardin; Cornelius A. Rietveld; Mark Sanders; Ute Stephan; Johan Wiklund (Small Business Economics, 2023)
The remarkable ascent of entrepreneurship witnessed as a scientific field over the last 4 decades has been made possible by entrepreneurship's ability to absorb theories, paradigms, and methods from other fields such as economics, psychology, sociology, geography, and even biology. The respectability of entrepreneurship as an academic discipline is now evidenced by many other fields starting to borrow from the entrepreneurship view. In the present paper, seven examples are given from this "pay back" development. These examples were first presented during a seminar at the Erasmus Entrepreneurship Event called what has the entrepreneurship view to offer to other academic fields? This article elaborates on the core ideas of these presentations and focuses on the overarching question of how entrepreneurship research impacts the development of other academic fields. We found that entrepreneurship research questions the core assumptions of other academic fields and provides new insights into the antecedents, mechanisms, and consequences of their respective core phenomena. Moreover, entrepreneurship research helps to legitimize other academic fields both practically and academically.
Keywords: B00; L26; M13; O30; 330; Entrepreneurship; Scientific impact; Academic fields